Dynamic optimization of countercurrent heat exchangers with phase change - Laiglecia, Juan Ignacio (2011)
Fil: Laiglecia, Juan Ignacio. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química (PLAPIQUI), CONICET. Bahía Blanca, Argentina